2014
DOI: 10.1086/678406
|View full text |Cite|
|
Sign up to set email alerts
|

The Paradox of Enrichment in Metaecosystems

Abstract: The paradox of enrichment has been studied almost exclusively within communities or metacommunities, without explicit nutrient dynamics. Yet local recycling of materials from enriched ecosystems may affect the stability of connected ecosystems. Here we study the effect of nutrient, detritus, producer, and consumer spatial flows-combined with changes in regional enrichment-on the stability of a metaecosystem model. We considered both spatially homogeneous and heterogeneous enrichment. We found that nutrient and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 114 publications
(128 reference statements)
3
82
0
Order By: Relevance
“…Previous empirical work had shown the importance of directional resource spatial flows between ecosystems for the maintenance of community structure and stability [2,7,40]. However, the temporal feedback that can occur over time had only been investigated in theoretical terms, using the meta-ecosystem framework [9,10,41]. Thus, in a second step we experimentally demonstrated that meta-ecosystem dynamics have implications for natural ecosystems under perturbation pressure because the way neighbouring ecosystems respond can directly affect community dynamics and functioning in connected ecosystems.…”
Section: Discussionmentioning
confidence: 93%
“…Previous empirical work had shown the importance of directional resource spatial flows between ecosystems for the maintenance of community structure and stability [2,7,40]. However, the temporal feedback that can occur over time had only been investigated in theoretical terms, using the meta-ecosystem framework [9,10,41]. Thus, in a second step we experimentally demonstrated that meta-ecosystem dynamics have implications for natural ecosystems under perturbation pressure because the way neighbouring ecosystems respond can directly affect community dynamics and functioning in connected ecosystems.…”
Section: Discussionmentioning
confidence: 93%
“…In simple two-patch meta-ecosystems, phase-locked cycles emerge from the positive feedback between recycling and passive movement of nutrients: more movement into a local ecosystem is correlated with increasing growth of the primary producer, thus destabilizing primary production. This prediction can be generalized to larger (many patch) meta-ecosystems 63 where the top-down control of biomass storage into inorganic form can stabilize a meta-ecosystem in the face of nutrient enrichment. For more complex finite and irregular topologies, the eigenvalues of the connectivity matrix, rather than more common topological metrics, predict the minimum movement of nutrients or of individuals that can destabilize the meta-ecosystem 64 .…”
Section: Meta-ecosystems: From the Local Cycling To Regional Fluxes Omentioning
confidence: 94%
“…Empirical research on material, energy and organismal flows across terrestrial and freshwater ecosystems has focused on the flux of small invertebrates (reviewed by Baxter et al ), litter (Wallace et al ), and migratory species (reviewed by Bauer and Hoye ). While we have gained considerable insight on meta‐ecosystem functioning by studying these key resource and consumer subsidies (reviewed by Allen and Wesner ), there have been recent calls to expand empirical studies to capture a greater breadth of the drivers and impacts of cross‐ecosystem fluxes (Soininen et al , Bakker et al , Gounand et al , Massol et al ). Here we fill an important gap in our knowledge of the functioning of meta‐ecosystems by demonstrating evidence for large terrestrial ungulate impacts on small stream functioning.…”
Section: Resultsmentioning
confidence: 99%